A Rapid Evidence Assessment of the impact of probation caseloads on reducing recidivism and other probation outcomes - Fox, Chris (Probation journal, 2022)
We undertook a Rapid Evidence Assessment to explore the existing empirical evidence relating to the impact of probation caseloads on recidivism. Over 3,000 potentially relevant papers were sifted from which five were deemed robust enough to be analysed in detail. All five were US studies which examined the impact of particular initiatives to reduce caseloads and were delivered by mainstream community-based probation officers. All recorded reductions in measured outcomes compared to comparators. Overall, although the number of robust studies remains quite small for such a key area of consideration, there appears to be a growing body of evidence that lower probation caseloads have a positive impact in terms of reducing reoffending in the USA. All five studies looked at a range of criminal justice outcomes including technical probation violations, violations for new arrests and reconvictions. Interestingly, although researchers were expecting to find a higher rate of probation violations among the cohorts supervised by probation officers with lower caseloads (due to the increased intensity of supervision), this did not turn out to be the case.